(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article examines the impact of AI on the transformation of labour relations. It is shown that AI systematically changes the structure of employment: redistributes functions between humans and machines, creates new professions, and redefines required skill sets. The «human–AI» model is explored. The paper highlights the polarisation of skill demand and the need for coordinated efforts among businesses, government, and workers. Conclusion: AI is a key factor in economic stability, enabling businesses to grow without increasing labour costs and fostering new employment models.